Manajemen Skala Prioritas Kehidupan Manusia dalam Perspektif Agama Islam - Satria Kharimul Qolbi; Sutrisno, Sutrisno (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
Every human activity has its own role and importance. In this case, a priority scale is required for each activity to be organized on a regular basis. Islam with all forms of teaching provides solutions to every problem of life without exception, as well as in terms of priorities. This research aims to explain the procedures for regulating the scale of priorities in human life according to the foundation of Islamic teachings. To arrive at that goal, the study used a dexatriptive-qualitative method with literature study techniques. In addition, the study also used a thematic approach by collecting Qur'anic verses that addressed a particular topic and ordered it wherever possible. The results of this study show that setting priorities begins with careful planning, solid organizing, proper implementation, and monitoring for control. All these stages are then integrated with the principle of priority jurispruding, namely the measure of truth highlighted in the Qur'an, the main priority over branch priorities, and the priority of people's rights to this right individually.